Use of Computed Tomography Scan to Rule Out Phantom Thrombus in the Left Atrial Appendage - Arabia, Luis; Lucino, Sergio; Tibaldi, José; Gambi, Diego Li; García, Romina; Pérez, Maria Eugenia; Bottello, Franco (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Occurrence of left atrial appendage (LAA) thrombus is a frequent complication of atrial fibrillation (AF) and it increase thromboembolic risk. Transesophageal echocardiography (TEE) is considered the gold standard to ensure that this chamber is thrombus free. Multidetector computed tomography (CT) scan has some advantages such the possibility to get 3D reconstruction and explore another structures in relationship with the LAA. However, lack of specificity in case of false positive images with filling defects due to slow velocities in the LAA. Methods and Results: 34 patiens with suspected thrombus by a previous CT scan or transesophageal echo were included in analisys. The aim of study was evaluated the utility of CT scan with delayed acquisition protocol to exclude LAA thrombus. In all of patients, complete LAA filling was observed, with a sensitivity, specificity and negative predictive value of 100% to differentiate circulatory stasis from thrombus. Conclusion: Perform a CT scan with a delayed acquisition protocol and in prone position are safe techniques to rule out fake thrombus.